Pertanggungjawaban Pidana Pemilik Hewan Peliharaan Terhadap Terjadinya Kecelakaan Lalu Lintas Dijalan Umum - Hendrikus Charly Cransen Senin; Jimmy Pello; Debi F. Ng. Fallo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Pets are animals kept by humans that must be cared for, looked after and have their living needs met and have a proper place. Negligence or neglect in the care of pets by pet owners is a form of error in criminal law as a result of someone's lack of care, resulting in something accidentally happening. So the author conducted this research with the aim of: (1) To find out whether pet owners whose negligence in looking after their pets cause traffic accidents on public roads can be punished. (2) To find out how the law provides sanctions for pet owners who are negligent in looking after their pets, causing traffic accidents on public roads and causing injuries and even death. The type of research used by the author is normative legal research. In this research, the sources of legal materials used by the author are primary legal material sources, secondary legal material sources, and tertiary legal material sources. The technique for collecting legal materials uses library research and then analyzed qualitatively. The findings specifically show that the regulations governing improper care of pets which cause traffic accidents on public roads are still subject to vague norms, so regulations are needed that regulate in more detail by referring to existing rules. Then there is the concept of criminal liability norms for pet owners who must fulfill the elements that constitute a causal offense, so that criminal liability can be sought through restorative justice and litigation.